The Effect of Mixing and Dissipation on A Lock-Exchange Flow Producedin A Channel of Constant Cross-Section - Tjipto Prastowo (Jurnal Fisika dan Aplikasinya, 2010)
Laboratory lock-exchanges of two fluids of different densities are used to examine the effects of mixing and dissipation on a dense current produced in a simple channel of constant width and height. Turbulent, small-scale mixing, induced by the flow instability at the interfacial layer, was observed above the current head. The mixing is found to affect the flow dynamics, in that the depth of the current is measured to be 0.36-0.47 H, less than a half of the full water depth H, defined as a theoretically predicted depth, and that the non-dimensional current speed is constant at 0.48 0.02, independent of all the external parameters. From these finding, we conclude that there is a loss of energy associated with turbulent dissipation and irreversible mixing and that bottom frictionplays a minor role in the propagation speed of the current.